New Archeomagnetic Directional Records From Iron Age Southern Africa (ca. 425–1550 CE) and Implications for the South Atlantic Anomaly - Vincent J. Hare; John A. Tarduno; Thomas Huffman; Michael Watkeys; Phenyo C. Thebe; Munyaradzi Manyanga; Richard K. Bono; Rory D. Cottrell (Geophysical Research Letters)
Abstract The paucity of Southern Hemisphere archeomagnetic data limits the resolution of paleosecular variation models. At the same time, important changes in the modern and historical field, including the recent dipole decay, appear to originate in this region. Here a new directional record from southern Africa is presented from analysis of Iron Age (ca. 425–1550 CE) archeological materials, which extends the regional secular variation curve back to the first millennium. Previous studies have identified a period of rapid directional change between 1225 and ∼1550 CE. The new data allow us to identify an earlier period of relatively rapid change between the sixth and seventh centuries CE. Implications for models of recurrent flux expulsion at the core‐mantle boundary are discussed. In addition, we identify a possible relationship of changes recorded in these African data with archeomagnetic jerks.